2010
DOI: 10.1029/2010gc003036
|View full text |Cite
|
Sign up to set email alerts
|

Melt‐induced seismic anisotropy and magma assisted rifting in Ethiopia: Evidence from surface waves

Abstract: The East African rift in Ethiopia is unique worldwide because it captures the final stages of transition from continental rifting to seafloor spreading. A recent study there has shown that magma intrusion plays an important role during the final stages of continental breakup, but the mechanism by which it is incorporated into the extending plate remains ambiguous: wide‐angle seismic data and complementary geophysical tools such as gravity analysis are not strongly sensitive to the geometry of subsurface melt i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
135
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 127 publications
(148 citation statements)
references
References 106 publications
(157 reference statements)
13
135
0
Order By: Relevance
“…NE of the TGD in the Red Sea and Gulf of Aden rifts in Afar, Gao et al (2010) use the backazimuthal variations in SKS splitting to show rift parallel anisotropy throughout the lithosphere. They interpret this as strain related structures such as magmatic intrusions, a similar interpretation as by Kendall et al (2005Kendall et al ( , 2006 and Bastow et al (2010) in the MER. Below the lithosphere, anisotropic fast directions parallel the N30-40°E trend of the African Superplume and are most sensibly interpreted as related to alignment of olivine in the asthenosphere induced by subhorizontal flow (e.g., Bastow et al, 2010;Gao et al, 2010;Kendall et al, 2006;Obrebski et al, 2010).…”
Section: Evidence From Broadband Seismologymentioning
confidence: 96%
See 1 more Smart Citation
“…NE of the TGD in the Red Sea and Gulf of Aden rifts in Afar, Gao et al (2010) use the backazimuthal variations in SKS splitting to show rift parallel anisotropy throughout the lithosphere. They interpret this as strain related structures such as magmatic intrusions, a similar interpretation as by Kendall et al (2005Kendall et al ( , 2006 and Bastow et al (2010) in the MER. Below the lithosphere, anisotropic fast directions parallel the N30-40°E trend of the African Superplume and are most sensibly interpreted as related to alignment of olivine in the asthenosphere induced by subhorizontal flow (e.g., Bastow et al, 2010;Gao et al, 2010;Kendall et al, 2006;Obrebski et al, 2010).…”
Section: Evidence From Broadband Seismologymentioning
confidence: 96%
“…In the MER, high-density splitting analysis of SKS phases in tandem with surface-wave studies is sensitive to a~20°change in orientation of strain fabrics from N30-40°E at the rift margins to N10°E along the rift axis. This change is interpreted as caused by the localisation of magma intrusion through the whole lithosphere toward the rift axis~2 Ma (Bastow et al, 2010;Kendall et al, 2005Kendall et al, , 2006. NE of the TGD in the Red Sea and Gulf of Aden rifts in Afar, Gao et al (2010) use the backazimuthal variations in SKS splitting to show rift parallel anisotropy throughout the lithosphere.…”
Section: Evidence From Broadband Seismologymentioning
confidence: 99%
“…This discrepancy between observed and predicted crustal thickness is likely to be partly the result of 'magma-compensated' thinning 7 , whereby extensive melt addition to the crust 3,4,6 has reduced net thinning, with a possible further contribution from magmatically accommodated extension 5 . However, the response of the lower part of the Ethiopian lithosphere to extension remains unclear and it is debated whether the lower plate has been preferentially thinned 14 , effectively compensating for the modest net crustal attenuation, or whether a significant thickness of the lithospheric mantle remains intact 17 .…”
Section: Conventional Rifting Modelsmentioning
confidence: 99%
“…Investigations of a variety of continental rifts and margins worldwide have revealed that a considerable volume of melt can intrude into the crust during continental breakup [1][2][3][4][5][6][7][8] , modifying its composition and thermal structure. However, it is unclear whether the cause of voluminous melt production at volcanic rifts is primarily increased mantle temperature or plate thinning 1,2,[8][9][10][11][12] .…”
mentioning
confidence: 99%
“…Thus, the initial phase of rifting above a mantle plume may be marked by a pulse of widespread dike intrusion (e.g., Renne et al, 1996;Fialko and Rubin, 1999;Klausen and Larsen, 2002). During the later stages of continental rifting, extension occurs principally by dike intrusion into a thinned lithosphere (Ebinger and Casey, 2001;Keranen et al, 2004;Rooney et al, 2005;Daly et al, 2008;Keir et al, 2009;Bastow et al, 2010;Ebinger et al, 2010;Wright et al, 2012), before a final stage of plate stretching and associated decompression melting characterizing the final stages of continentocean transition (e.g., Bastow and Keir, 2011). Key unresolved questions remain concerning the geochemical signature(s) of the melt sources during the initial stages of continental rifting, and the evolution of these sources as rifting continues.…”
Section: Introductionmentioning
confidence: 99%